1997
DOI: 10.1063/1.53619
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of diffractive DIS

Abstract: The recent progress in the QCD theory of diffractive DIS (DDIS) is reviewed. We place emphasis on pQCD scales, diffractive factorization breaking, jet and charm production and new fundamental observables which are becoming accessible with the Leading Proton Spectrometers (LPS) of ZEUS and H1. DIFFRACTIVE STRUCTURE FUNCTIONSThis is an opening talk on diffraction at DIS'97 and we start with definitions. The longitudinal (L) and the two transverse (T) polarizations of the exchanged photon define the four componen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Color dipole interactions Since in small-x interactions it is rather the qq fluctuation of the photon which interacts with the target proton, it is natural to view the interaction as that of a color dipole with the proton (Nikolaev and Zakharov, 1994;Nikolaev and Zakharov, 1997;Wüsthoff, 1997b;Bia las and Peschanski, 1996). Bia las and Peschanski (1996) have extended the dipole approach assuming that the proton also consists of color dipoles.…”
Section: Qcd Inspired Models Of Lrg Productionmentioning
confidence: 99%
“…Color dipole interactions Since in small-x interactions it is rather the qq fluctuation of the photon which interacts with the target proton, it is natural to view the interaction as that of a color dipole with the proton (Nikolaev and Zakharov, 1994;Nikolaev and Zakharov, 1997;Wüsthoff, 1997b;Bia las and Peschanski, 1996). Bia las and Peschanski (1996) have extended the dipole approach assuming that the proton also consists of color dipoles.…”
Section: Qcd Inspired Models Of Lrg Productionmentioning
confidence: 99%
“…Such a suppression of the cross section is usually attributed to rescattering, or absorptive corrections [87][88][89][90], which are Table 10 Cross section of elastic ρ 0 photoproduction on the pion, γ π + → ρ 0 π + , extracted in the one-pion-exchange approximation using three different samples: full sample, OPE1 and OPE2. The first uncertainty represents the full experimental error and the second is the model error coming from the pion flux uncertainty (see text).…”
Section: γ π Cross Sectionmentioning
confidence: 99%
“…Since,however, fixed-x L fits, by construction, represent the best parametrisations of the data and Eqs. (18)(19)(20) are interpreted as a mere interpolating tool, we require that the accuracy of the x L -combined fit does not exceeds the one of the fixed-x L fits. We found that a conservative χ 2 = 9 criterion matches these requirements, as shown in Fig.…”
Section: Error Estimation and Propagationmentioning
confidence: 99%
“…An intensive physics program with forward neutron tagging has been pursued at HERA as well, where recent results [14,15] show that around 8 % of the DIS events contain a forward neutron. These data are crucial in testing the limiting fragmentation hypothesis [16] and have been used as benchmark in a number of Regge-based models [17][18][19][20][21][22][23] which mainly concentrate on the modelisation of forward neutron production mechanisms. In the present paper we adopt instead a complementary approach and no modelisation of neutron production mechanisms is attempted.…”
Section: Introductionmentioning
confidence: 99%